The Influence of Filmic Representations on Narratives of Place and Tourist Destination Image : Johannesburg, South Africa. - Harris, Karen Leigh (University of Pretoria, 2022)
Dissertation (MSocSci (Heritage and Cultural Tourism))--University of Pretoria, 2022.